Effect of Relaxation Guided Imagery on Premenstrual Syndrome in Adolescent - Saragih, Hanna Sriyanti; Hutagaol, Hotma Sauhur (Jurusan Keperawatan FIKES UNSOED, 2016)
Menstruation is a periodical bleeding according to its cycle. Menstrual pain is a painful feeling during menstruation at the lower region that accompanying menstruation, before, or after menstruation. Guided Imagery relaxation is a common method which is the utmost method especially for patients experiencing pain. Therefore a study to examine the effect of relaxation therapy in relieving pain is required. This study was to examine the discrepancy of menstrual pain level before and after guided imagery relaxation performed. This quasi experiment with pre and posttest control group design was to investigate the effect of a guided imagery relaxation therapy on the menstrual pain. Data were analyzed by Mann-Whitney test with significant threshold set to 0.05. Results indicated that the experiment group experienced menstrual pain score mean 2.6 Â± 0.5, while in the control group 4.6 Â± 0.6. It concluded that guided imagery relaxation effect on menstrual pain.